Preparation method of acoustic resonance driven glycyrrhizic acid nanocomposite responsive gel
The method of preparing glycyrrhizic acid nanocomposite responsive gel driven by acoustic resonance solves the problems of low drug absorption and solvent residue in UC treatment, and achieves efficient and uniform targeted drug delivery and high concentration retention at the site of colon inflammation, thereby enhancing the therapeutic effect and conforming to the trend of green treatment.
Patent Information
- Application Number
- CN202511401947.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-28
- Publication Date
- 2026-01-06
AI Technical Summary
Existing UC treatment drugs have low absorption rates in the gastrointestinal tract. Traditional delivery methods using organic solvents result in solvent residues and uneven drug mixing, making it difficult to target the inflamed areas of the colon, and also leading to drug resistance and adverse reactions.
An acoustic resonance-driven method for preparing glycyrrhizic acid nanocomposite responsive gels was developed. This method utilizes low-frequency acoustic resonance technology to self-assemble glycyrrhizic acid and water-insoluble natural small molecule drugs in an aqueous phase, forming a negatively charged nanocomposite. The gel is then formed by the attraction of positive and negative charges and the response of calcium ions, thus achieving targeted treatment of colonic inflammation sites.
It increases the concentration and residence time of drugs at the site of colon inflammation, enhances the therapeutic effect, reduces the risk of solvent residue, conforms to the trend of green development, and achieves efficient and uniform drug delivery.
Smart Images

Figure CN121265518A_ABST
Abstract
Description
Technical Field
[0001] This application belongs to the field of biotechnology and new medicine, specifically relating to a method for preparing an acoustic resonance-driven glycyrrhizic acid nanocomposite responsive gel, which is used for a novel drug delivery and treatment strategy for colitis. Background Technology
[0002] Ulcerative colitis (UC) is a chronic, relapsing disease that begins in the rectum and typically extends proximally through part or all of the colon in a continuous manner. Treatment for UC usually involves two routes of administration: oral and rectal. Oral administration is the simplest route for treating colitis and is suitable for patients with more extensive colitis lesions. However, due to the complex body environment, without any delivery system or prodrug conjugate, the oral medication is first digested by gastric juices, then enters the small intestine, and is transferred towards the ileum and colon. During this process, most of the drug is absorbed by the stomach and small intestine, with only a small portion reaching the terminal ileum and colon to exert its effect; the remainder is directly excreted. Therefore, drug utilization is low, and the therapeutic effect is not significant. Compared to oral administration, rectal administration has the advantages of overcoming fewer physiological barriers to reach the lesion, achieving higher local concentrations, reducing hepatic absorption and metabolism, significantly improving drug efficacy, and reducing drug toxicity.
[0003] Currently, conventional drugs used to treat ulcerative colitis (UC) mainly include sulfasalazine-pyridine salicylate preparations, corticosteroids, and immunosuppressants. However, these treatments often involve increased drug resistance and adverse reactions. Therefore, finding effective and low-toxicity preventative drugs has become a research hotspot in recent years. Natural products, as compounds extracted from nature, have great potential in disease treatment. Many natural products possess anti-inflammatory, antioxidant, and immunomodulatory effects, such as berberine, ursolic acid, baicalin, luteolin, curcumin, baicalin, and ginsenoside Rh2. However, the poor water solubility of most of these compounds limits their absorption in the gastrointestinal tract.
[0004] Some existing drugs utilize compounds with good solubility to carry natural products (berberine, ursolic acid, baicalin, luteolin, curcumin, baicalin, ginsenoside Rh2) to achieve targeted therapeutic effects. However, the carrying process requires the use of organic solvents, which can easily leave solvent residues and does not conform to the trend of green development. At the same time, the mixtures obtained by existing carrying methods are not uniformly mixed, which affects the therapeutic effect of the drug.
[0005] In addition, when inflammation occurs in the colon, the site of inflammation produces proteins with a large number of positive charges, such as transferrin and antimicrobial peptides. Furthermore, neutrophils also migrate to the site of inflammation and release calprotectin.
[0006] Therefore, developing a targeted drug preparation method that does not use organic solvents and carries a uniformly mixed natural product has great market potential. At the same time, a nanocomposite that can target the increased content of positively charged proteins and calprotectin in the inflammatory sites of ulcerative colitis and achieve targeted aggregation and responsive adhesion, thereby achieving a good therapeutic effect on colitis, has important clinical significance. Summary of the Invention
[0007] The purpose of this application is to address the problems of the prior art by providing a method for preparing an acoustic resonance-driven glycyrrhizic acid nanocomposite responsive gel.
[0008] To solve the technical problem, the technical solution of this application is: a method for preparing an acoustic resonance-driven glycyrrhizic acid nanocomposite responsive gel, comprising the following steps: Step 1: Weigh glycyrrhizic acid powder and water-insoluble natural small molecule drug into a resonant vessel, add deionized water to form a premixed solution. The mass ratio of glycyrrhizic acid powder to water-insoluble natural small molecule drug is 20:1~10:12, and the volume ratio of deionized water to glycyrrhizic acid powder is 1ml:10mg. Step 2: Fix the resonant vessel of the above premixed liquid in a low-frequency acoustic resonance instrument to resonate and obtain a resonant mixed solution; the resonance parameters are: the resonance frequency is low frequency 20~100Hz, when the resonance curve is horizontal, a high frequency harmonic of 5~10kHz is superimposed, the acceleration is 5~100g, the resonance treatment time is 5~60 minutes, and the temperature is 25±20℃. Step 3: The resonant mixed solution is subjected to gradient centrifugation to remove precipitates and unencapsulated crystals, resulting in a glycyrrhizic acid nanocomposite solution carrying a water-insoluble natural small molecule drug. The glycyrrhizic acid nanocomposite solution is negatively charged and can form a responsive gel with calcium ion solution.
[0009] Preferably, the water-insoluble natural small molecule drug in step 1 is berberine, ursolic acid, baicalin, luteolin, curcumin, baicalin or ginsenoside Rh2.
[0010] Preferably, the water-insoluble natural small molecule drug is baicalein, and the mass ratio of glycyrrhizic acid powder to baicalein is 20:1 to 10:4.
[0011] Preferably, the specific steps of resonance in step 2 are as follows: set the resonance frequency to a low frequency of 20~100Hz, the acceleration to 5~20g, and after the resonance intensity curve stabilizes at a horizontal level, superimpose a high frequency harmonic of 5~10kHz, increase the acceleration to 20~100g, and perform resonance treatment for 30 minutes to drive the resonance self-assembly of glycyrrhizic acid powder and water-insoluble natural small molecule drugs.
[0012] Preferably, the gradient centrifugation parameters in step 3 are 4000 rpm × 10 min and 3000 rpm × 5 min.
[0013] Preferably, the glycyrrhizic acid nanocomposite in the glycyrrhizic acid nanocomposite solution has a particle size of 632.76±10.48 nm and the glycyrrhizic acid nanocomposite is negatively charged with a charge of -83.22 mV.
[0014] Preferably, the glycyrrhizic acid nanocomposite solution transforms from a solution state to a gel state after contacting with a calcium ion solution, forming a responsive gel.
[0015] Preferably, the responsive gel has a loose porous structure, which can increase the loading of glycyrrhizic acid nanocomposite and achieve sustained and controlled release of glycyrrhizic acid nanocomposite.
[0016] Compared with the prior art, the advantages of this application are: (1) In this application, glycyrrhizic acid is used as the drug delivery system, and berberine, ursolic acid, baicalin, luteolin, curcumin, baicalin or ginsenoside Rh2 are used as water-insoluble natural small molecule drugs. Glycyrrhizic acid is an amphiphilic compound composed of one molecule of glycyrrhetinic acid and two molecules of glucuronic acid. In an aqueous environment, it can form a hydrophobic cavity to encapsulate water-insoluble natural small molecule drugs, forming a glycyrrhizic acid nanocomplex solution, while improving the solubility of water-insoluble natural small molecule drugs such as baicalin. (2) The glycyrrhizic acid nanocomposite solution of this application is negatively charged and can be adsorbed to the inflamed area of colon by the mutual attraction of positive and negative charges. At the same time, it binds to calcium ions in the calprotectin of the inflamed area, thereby changing from a solution state to a hydrogel. The hydrogel adheres tightly to the inflamed area, reducing drug leakage and prolonging the drug's action time at the lesion. (3) This application uses glycyrrhizic acid derived from natural plants as a carrier and a therapeutic drug, and baicalein, an active ingredient of traditional Chinese medicine, as a representative drug. The two are driven by low-frequency acoustic resonance to form a GA@BA nanocomposite. Compared with traditional drugs, after oral administration or enema, the GA@BA nanocomposite can target the characteristics of the inflammatory microenvironment of the colon with a large number of positive charges and increased calcium ion concentration, accumulate at the site of colon inflammation and respond to calcium ions to form a gel, thereby increasing the concentration and retention time of the drug at the site of colon inflammation. (4) This application innovatively introduces low-frequency acoustic resonance technology, abandons traditional organic solvents (such as ethanol, dichloromethane, etc.), and achieves drug self-assembly with pure water phase, eliminating the risk of solvent residue and conforming to the green trend; compared with the traditional ultrasonic method, this application dynamically regulates the intermolecular forces (hydrogen bonds, hydrophobic interactions) through vibration-acoustic coupling field to achieve particle size uniformity (PDI≤0.25) and improve the apparent solubility of water-insoluble drugs; compared with the traditional glycyrrhizic acid nanoparticle preparation method, the processing time of this application can be shortened to 30 minutes, significantly reducing energy consumption, and can achieve kilogram-level mass production in one go, which not only provides an efficient treatment plan for ulcerative colitis, but also sets a new benchmark of "green, efficient and scalable" in the field of nanoparticle preparation, and has broad clinical application and commercialization prospects. Attached Figure Description
[0017] Figure 1 This is a flowchart of a method for preparing an acoustic resonance-driven glycyrrhizic acid nanocomposite responsive gel according to this application; Figure 2 This is a photograph of the glycyrrhizic acid nanocomposite solution loaded with different drugs in Example 1 of this application; Figure 3 This application presents physical images of glycyrrhizic acid nanocomposite solutions obtained by different feeding ratios of glycyrrhizic acid and baicalein in Example 1 of this application, along with results on particle size and dispersion coefficient. Figure 4 These are comparative images of the GA@BA nanocomposite solution prepared using a low-frequency acoustic resonance instrument in Example 2 of this application, the BA solution prepared by the traditional ultrasonic method, and the GA&BA mixed solution. Figure 5 This is a particle size and charge detection diagram of the GA@BA nanocomposite solution in Example 2 of this application; Figure 6 This is an evaluation graph showing the changes in particle size and dispersibility of the GA@BA nanocomposite solution after 28 days of storage in Example 2 of this application; Figure 7 These are comparison images of the GA@BA nanocomposite solution before and after mixing with calcium ion solution in Example 3 of this application, as well as the cryo-electron microscopy results of the nanocomposite solution and the scanning electron microscopy results of the nanocomposite solution after it forms a gel. Figure 8 This is a mechanical strength diagram of the GA@BA nanocomposite solution after gel formation in Example 3 of this application; Figure 9 This is a comparison graph showing the retention time of Cy5.5 and GA@Cy5.5 in mice with ulcerative colitis in Example 4 of this application; Figure 10 These are intestinal endoscopy images of mice in each group after DSS-induced ulcerative colitis in Example 4 of this application; Figure 11 This refers to the changes in colon length in mice in each group after DSS-induced ulcerative colitis in Example 4 of this application. Figure 12 These are HE-stained images of colon tissue from various groups of mice after DSS-induced ulcerative colitis in Example 4 of this application. Detailed Implementation
[0018] The present application is described in detail below with reference to the accompanying drawings and specific embodiments, but the present application is not limited to these embodiments. The present application covers any alternatives, modifications, equivalent methods, and solutions made within the spirit and scope of the present application. To provide the public with a thorough understanding of the present application, specific details are described in detail in the following embodiments, but those skilled in the art will fully understand the present application even without these detailed descriptions.
[0019] Glycyrrhizic acid, as one of the effective components of licorice root, has anti-inflammatory and antiviral effects. Baicalein is a yellow needle-shaped crystal extracted from the rhizome of Scutellaria baicalensis. Pharmacological studies have shown that baicalein has a wide range of activities, including scavenging free radicals, inhibiting inflammatory signaling pathways, and binding to key viral proteins. However, the poor water solubility of baicalein limits its clinical application. This application addresses this issue by conducting research and development.
[0020] like Figure 1 As shown, this application discloses a method for preparing an acoustic resonance-driven glycyrrhizic acid nanocomposite responsive gel, comprising the following steps: Step 1: Weigh glycyrrhizic acid powder and water-insoluble natural small molecule drug into a resonant vessel, add deionized water to form a premixed solution. The mass ratio of glycyrrhizic acid powder to water-insoluble natural small molecule drug is 20:1~10:12, and the volume ratio of deionized water to glycyrrhizic acid powder is 1ml:10mg. Step 2: Fix the resonant vessel of the above premixed liquid in a low-frequency acoustic resonance instrument to resonate and obtain a resonant mixed solution; the resonance parameters are: the resonance frequency is low frequency 20~100Hz, when the resonance curve is horizontal, a high frequency harmonic of 5~10kHz is superimposed, the acceleration is 5~100g, the resonance treatment time is 5~60 minutes, and the temperature is 25±20℃. Step 3: The resonant mixed solution is subjected to gradient centrifugation to remove precipitates and unencapsulated crystals, resulting in a glycyrrhizic acid nanocomposite solution carrying a water-insoluble natural small molecule drug. The glycyrrhizic acid nanocomposite solution is negatively charged and can form a responsive gel with calcium ion solution.
[0021] Preferably, the water-insoluble natural small molecule drug in step 1 is berberine, ursolic acid, baicalin, luteolin, curcumin, baicalin or ginsenoside Rh2.
[0022] Preferably, the water-insoluble natural small molecule drug is baicalein, and the mass ratio of glycyrrhizic acid powder to baicalein is 20:1 to 10:4.
[0023] Preferably, the specific steps of resonance in step 2 are as follows: set the resonance frequency to a low frequency of 20~100Hz, the acceleration to 5~20g, and after the resonance intensity curve stabilizes at a horizontal level, superimpose a high frequency harmonic of 5~10kHz, increase the acceleration to 20~100g, and perform resonance treatment for 30 minutes to drive the resonance self-assembly of glycyrrhizic acid powder and water-insoluble natural small molecule drugs.
[0024] Preferably, the gradient centrifugation parameters in step 3 are 4000 rpm × 10 min and 3000 rpm × 5 min.
[0025] Preferably, the glycyrrhizic acid nanocomposite in the glycyrrhizic acid nanocomposite solution has a particle size of 632.76±10.48 nm and the glycyrrhizic acid nanocomposite is negatively charged with a charge of -83.22 mV.
[0026] Preferably, the glycyrrhizic acid nanocomposite solution transforms from a solution state to a gel state after contacting with a calcium ion solution, forming a responsive gel.
[0027] Preferably, the responsive gel has a loose porous structure, which can increase the loading of glycyrrhizic acid nanocomposite and achieve sustained and controlled release of glycyrrhizic acid nanocomposite.
[0028] This application uses baicalein (BA) as the water-insoluble natural small molecule drug and glycyrrhizic acid nanocomposite as GA@BA. Because glycyrrhizic acid has an amphiphilic structure, it can self-assemble into a nanocomposite in water. Its hydrophobic core can carry the water-insoluble natural small molecule drug, thereby improving its solubility. Furthermore, it can also be used to carry other water-insoluble natural small molecule drugs such as berberine, ursolic acid, curcumin, luteolin, baicalin, and ginsenoside Rh2.
[0029] Taking baicalein as an example, appropriate amounts of glycyrrhizic acid and baicalein were weighed at a mass ratio of 10:2 and added to deionized water to form a premix. The premix was then resonated using a low-frequency acoustic resonance instrument with a base frequency of 50Hz, a superimposed high-frequency harmonic frequency of 5-10kHz, an acceleration of 20g, a treatment time of 30 minutes, and a temperature controlled at 25±2℃. After resonance, a pale yellow-green GA@BA nanocomposite was obtained. In the nanocomposite, the amphiphilic glycyrrhizic acid acts as a carrier, encapsulating baicalein within a hydrophobic core through hydrophobic interactions, thereby significantly improving the apparent solubility of baicalein.
[0030] This nanocomposite solution can be taken orally or via enema. When the colon is inflamed, the concentration of calcium ions at the site of inflammation increases, and the colon carries a large number of charges. The GA@BA nanocomposite aggregates towards the site of colon inflammation through the attraction between positive and negative charges. After combining with the calcium ions at the site of inflammation, it transforms into a gel and adheres to the surface of the inflamed colon, increasing the local drug concentration and prolonging the drug's retention time in the colon.
[0031] Example 1 Preparation of glycyrrhizic acid nanocomposite solution: Glycyrrhizic acid nanocomposites were prepared using an acoustic resonance-driven method: 10 mg of glycyrrhizic acid and 4 mg each of berberine, ursolic acid, baicalein, luteolin, curcumin, baicalin, and ginsenoside Rh2 were accurately weighed, added to 1 mL of deionized water, mixed thoroughly, and fixed in a low-frequency acoustic resonance instrument. A high-frequency harmonic (5–10 kHz) was superimposed at a base frequency of 50 Hz. The initial acceleration was 5 g. After the resonance intensity curve stabilized, the acceleration was increased to 20–30 g, and the resonance treatment lasted for 30 minutes to promote drug dispersion and the resonant self-assembly of glycyrrhizic acid and water-insoluble natural small molecule drugs. Precipitation and unloaded crystals were removed by gradient centrifugation (4000 rpm × 10 min and 3000 rpm × 5 min) to obtain glycyrrhizic acid nanocomposite solutions loaded with different drugs, as shown below. Figure 2 As shown.
[0032] like Figure 3 The image shown is a photograph of glycyrrhizic acid nanocomposite solutions obtained with different feed ratios of glycyrrhizic acid and baicalein, along with the results of particle size and dispersion coefficient. Figure 3 Image a shows a physical image of glycyrrhizic acid nanocomposite solutions obtained with different feed ratios of glycyrrhizic acid and baicalein. Figure 3 In the figure, b represents the particle size and dispersion coefficient (PDI) results for different feed ratios. The feed ratio can be selected according to the needs.
[0033] Example 2 (1) Properties and characterization of GA@BA nanocomposites: The preparation of GA@BA nanocomposites using low-frequency acoustic resonance significantly improved the apparent solubility of baicalin. like Figure 4 As shown, Figure 4 Image a shows a comparison of the GA@BA nanocomposite solution prepared using a low-frequency acoustic resonance instrument, the BA solution prepared using the traditional ultrasonic method, and the GA&BA mixed solution. It can be seen that the GA@BA nanocomposite solution prepared using low-frequency acoustic resonance is uniformly mixed, and no baicalin precipitation is visible to the naked eye compared to the traditional ultrasonic method. The content of baicalin in the solution was detected by high-performance liquid chromatography. Figure 4In Figure b, the results of baicalein solubility in different solutions are shown. It can be found that the acoustic resonance technology greatly improves the apparent solubility of baicalein. In the ultrasound-treated baicalein mono-group (BA) and glycyrrhizic acid plus baicalein group (GA&BA), baicalein is almost insoluble in water (ns indicates no difference; **** indicates extremely significant difference, p<0.0001).
[0034] (2) Evaluation of the particle size and stability of GA@BA nanocomposites: like Figure 5 As shown, the particle size of the GA@BA nanocomposite solution was detected using a particle size analyzer. Figure 5 Figure a shows that the PDI of the GA@BA nanocomposite is 0.24, indicating a uniform particle size distribution of 632.76±10.48 nm and a negative charge. Figure 5 The value of b in the diagram is -83.22 mV. (For example...) Figure 6 The figure shows the evaluation of particle size and dispersibility changes of the GA@BA nanocomposite solution after 28 days of storage. The prepared GA@BA nanocomposite solution was placed at 4℃ for 28 days for stability testing. By measuring the changes in particle size and dispersibility, it was observed that GA@BA remained stable within 28 days.
[0035] Example 3 (1) Microstructure of GA@BA nanocomposite and gel and evaluation of calcium ion responsiveness: like Figure 7 The images shown are comparisons of the GA@BA nanocomposite solution before and after mixing with calcium ion solution, as well as cryo-electron microscopy results of the nanocomposite solution and scanning electron microscopy results of the nanocomposite solution after gel formation. Figure 7 Image 'a' shows the structure of the GA@BA nanocomposite solution under cryo-electron microscopy; the image reveals a linear structure. Figure 7 As shown in Figure b, when calcium chloride solution is added to the solution, the GA@BA nanocomposite solution transforms into a gel with increased viscoelasticity. At this point, when the sample bottle is inverted, GA@BA adheres to the bottom of the sample bottle, while the GA@BA nanocomposite solution exhibits fluidity and flows towards the cap. Figure 7 In the middle c, the scanning electron microscope (SEM) result of the GA@BA gel shows that the GA@BA gel exhibits a loose and porous structure.
[0036] (2) Mechanical characteristics of GA@BA gel: like Figure 8 The figure shows the mechanical strength of the GA@BA nanocomposite solution after it has formed a gel. Figure 8As shown in Figure a, after the GA@BA nanocomposite solution formed a gel in the calcium ion solution microenvironment, its viscosity was tested using a rotational rheometer. The results showed that, compared to the GA@BA nanocomposite solution, the viscosity increased from 25.1 Pa·s to 898 Pa·s after GA@BA was induced to form a gel with calcium chloride. Figure 8 In the middle, b represents the dynamic frequency scan result displayed in the range of 0.1~100 rad / s. -1 Within the range, energy storage modulus (G ’ ) is always greater than the loss modulus (G) ” This confirms that GA@BA gel exhibits elastic behavior. Figure 8 The middle c shows that when the amplitude exceeds 100%, the G of GA@BA gel... ” >G', the transition of GA@BA gel to solution state. Figure 8 The results of the thixotropic experiment showed that, at an amplitude of 0.1%, the G of GA@BA... ’ >G ” When the amplitude is 100%, G ” >G', when the amplitude changes back to 0.1%, G ’ >G ” The results demonstrate that the GA@BA hydrogel possesses self-healing properties. These results indicate that the GA@BA nanocomposite exhibits excellent permeability and inflammatory microenvironment-responsive gel-forming ability.
[0037] Example 4 (1) Evaluation of the retention time of the nanocomposite in mice with ulcerative colitis: Ulcerative colitis (UC) was induced in 6-8 week old C57BL / 6 mice by allowing them free access to 2.5% (w / v) sodium dextran sulfate (DSS) in drinking water for 7 days. A fluorescent dye (Cy5.5) was used to represent water-insoluble small molecule drugs to evaluate drug retention time. Subsequently, mice were orally administered 0.2 ml of a solution of free Cy5.5 and GA@Cy5.5 nanocomposite, and the mouse intestines were harvested at different time points for in vivo imaging to observe the distribution of the GA@Cy nanocomposite within the mouse intestine. Figure 9 As shown, GA@Cy5.5 has a longer retention time in the mouse intestine compared to free Cy5.5.
[0038] (2) Evaluation of the therapeutic effect of GA@BA on DSS ulcerative colitis mice: Mice were induced to develop ulcerative colitis using the same method. After successful modeling, mice were treated for six days with 0.2 ml of the drug once daily. Mice were divided into seven groups: normal (Control group), DSS + deionized water (dd H2O group), DSS + Free-GA group, DSS + Free-BA group, DSS + GA & BA group, DSS + GA@BA group, and DSS + enema (GA@BA Clyster group). The corresponding GA concentration was 10 mg / ml and BA concentration was 2 mg / ml. After treatment, the colonic mucosa of each group was observed endoscopically. Figure 10 As shown, compared to the normal intestinal tissue in the Control group, the intestinal mucosa in the dd H2O group showed hemorrhage and ulceration. Mice in the GA@BA and GA@BA Clyster groups showed significant repair of the colonic mucosa after oral treatment with GA@BA, with the intestinal mucosa approaching normal. Subsequently, mice in each group were sacrificed, and colonic tissue from each group was removed and its length measured. Figure 11 As shown, compared to the dd H2O group, oral or enema treatment with GA@BA significantly promoted the recovery of colon length in mice with ulcerative colitis. Subsequently, colon tissue from each group of mice was prepared into histological sections, and the pathological changes in the colon tissue of each group were observed, such as... Figure 12 As shown, the dd H2O group mice showed extensive damage to the intestinal epithelium of the colon, infiltration of inflammatory cells, a significant reduction in goblet cells, and large-scale disappearance of glands. After oral or enema treatment with GA@BA, the colonic tissue of the GA@BA group and the GA@BAClyster group showed significant recovery, with intact colonic crypts, close to the normal control group, indicating that the inflammation was reduced.
[0039] This application uses glycyrrhizic acid (GA) as the drug delivery system, and berberine, ursolic acid, baicalin, luteolin, curcumin, baicalin or ginsenoside Rh2 as water-insoluble natural small molecule drugs. Glycyrrhizic acid is an amphiphilic compound composed of one molecule of glycyrrhetinic acid and two molecules of glucuronic acid. In an aqueous environment, it can form a hydrophobic cavity to encapsulate water-insoluble natural small molecule drugs, forming a glycyrrhizic acid nanocomplex solution, while improving the solubility of water-insoluble natural small molecule drugs such as baicalin.
[0040] The glycyrrhizic acid nanocomposite solution of this application is negatively charged and can be adsorbed to the site of colon inflammation by the mutual attraction of positive and negative charges. At the same time, it binds to calcium ions in the calprotectin of the inflamed site, thereby transforming from a solution state into a hydrogel. The hydrogel adheres tightly to the inflamed site, reducing drug leakage and prolonging the drug's action time at the lesion.
[0041] This application uses glycyrrhizic acid, derived from natural plants, as a carrier and therapeutic drug, and baicalein, an active ingredient of traditional Chinese medicine, as a representative drug. The two are driven by low-frequency acoustic resonance to form a GA@BA nanocomplex. Compared with traditional drugs, the GA@BA nanocomplex, when taken orally or administered as an enema, can target the characteristics of the inflammatory microenvironment of the colon, which has a large number of positive charges and increased calcium ion concentration. It can accumulate at the site of colon inflammation and respond to calcium ions to form a gel, thereby increasing the concentration and retention time of the drug at the site of colon inflammation.
[0042] This application innovatively introduces low-frequency acoustic resonance technology, abandoning traditional organic solvents (such as ethanol and dichloromethane), and achieves drug self-assembly using a pure aqueous phase, eliminating the risk of solvent residue and conforming to the trend of green development. Compared with the traditional ultrasonic method, this application achieves uniform particle size (PDI≤0.25) by dynamically controlling intermolecular forces (hydrogen bonds and hydrophobic interactions) through vibration-acoustic coupling field, thereby improving the apparent solubility of water-insoluble drugs. Compared with the traditional glycyrrhizic acid nanoparticle preparation method, the processing time of this application can be shortened to 30 minutes, significantly reducing energy consumption, and kilogram-level mass production can be achieved in one go. This not only provides an efficient treatment solution for ulcerative colitis, but also sets a new benchmark of "green, efficient, and scalable" in the field of nanoparticle formulations, with broad prospects for clinical application and commercialization.
[0043] The preferred embodiments of this application have been described in detail above. However, this application is not limited to the above embodiments. Within the scope of knowledge possessed by those skilled in the art, various changes can be made without departing from the spirit of this application.
[0044] Many other changes and modifications can be made without departing from the concept and scope of this application. It should be understood that this application is not limited to the specific embodiments, and the scope of this application is defined by the appended claims.
Claims
1. A method for preparing an acoustic resonance driven glycyrrhizin nanocomposite responsive gel, characterized by, The method comprises the following steps: Step 1: The glycyrrhizic acid powder and the water-insoluble natural small molecule drug are weighed and placed in a resonance vessel, deionized water is added to form a premix, the mass ratio of the glycyrrhizic acid powder and the water-insoluble natural small molecule drug is 20:1-10:12, and the dosage ratio of the deionized water to the glycyrrhizic acid powder is 1ml:10mg; Step 2: The resonance vessel with the premix is fixed in a low-frequency acoustic resonance instrument for resonance to obtain a resonance mixed solution; the resonance parameters are as follows: the resonance frequency is low frequency 20-100Hz, when the resonance curve is horizontal, 5-10kHz high frequency harmonic is superimposed, the acceleration is 5-100g, the resonance treatment time is 5-60 minutes, and the temperature is 25±20℃; Step 3: The resonance mixed solution is subjected to gradient centrifugation to remove the precipitate and the non-encapsulated crystal to obtain a glycyrrhizic acid nanocomposite solution loaded with the water-insoluble natural small molecule drug; the glycyrrhizic acid nanocomposite solution is negatively charged, and the glycyrrhizic acid nanocomposite solution can form a responsive gel with a calcium ion solution.
2. The method of claim 1, wherein the method is characterized by: The water-insoluble natural small molecule drug in step 1 is berberine, ursolic acid, baicalein, luteolin, curcumin, or paeoniflorin or ginsenoside Rh2.
3. The method of claim 2, wherein the method is characterized by: The water-insoluble natural small molecule drug is baicalein, and the mass ratio of the glycyrrhizic acid powder to the baicalein is 20:1-10:
4.
4. The method of claim 1, wherein the method is characterized by: In step 2, the resonance specific steps are as follows: the resonance frequency is set to low frequency 20-100Hz, the acceleration is 5-20g, when the resonance intensity curve is stable and horizontal, 5-10kHz high frequency harmonic is superimposed, the acceleration is increased to 20-100g, the resonance treatment is performed for 30 minutes, and the resonance self-assembly of the glycyrrhizic acid powder and the water-insoluble natural small molecule drug is driven.
5. The method of claim 1, wherein the method is characterized by: In step 3, the gradient centrifugation parameters are 4000rpm×10min and 3000rpm×5min.
6. The method of claim 1, wherein the method is characterized by: The glycyrrhizic acid nanocomposite in the glycyrrhizic acid nanocomposite solution has a particle size of 632.76±10.48nm, and the glycyrrhizic acid nanocomposite is negatively charged with a charge of-83.22mV.
7. The method of claim 1, wherein the method is characterized by: The glycyrrhizic acid nanocomposite solution changes from a solution state to a gel state after being contacted with a calcium ion solution to form a responsive gel.
8. The method of claim 7, wherein the method is characterized by: The responsive gel has a loose porous structure, the loose porous structure can increase the loading capacity of the glycyrrhizic acid nanocomposite, and the slow release and controlled release of the glycyrrhizic acid nanocomposite are realized.
